(untitled) (Current Problems in Rail Vehicles, 2021)
The article looks into the use of artificial intelligence (AI) methods, specifically image detection and classification in railway transport. The introductory chapters describe the possibilities that AI currently offers in various fields of science and industry, followed by a description of the use of AI in the Custom Vision environment for image classification of railway track signals. In the end, there is an evaluation of the simulation of the use of AI and a consideration of the possible use in real operation.